2021
DOI: 10.2174/1874306402115010001
|View full text |Cite
|
Sign up to set email alerts
|

Current Utility of Sequential Organ Failure Assessment Score: A Literature Review and Future Directions

Abstract: The Sequential Organ Failure Assessment (SOFA) score is commonly used in the Intensive Care Unit (ICU) to evaluate, prognosticate and assess patients. Since its validation, the SOFA score has served in various settings, including medical, trauma, surgical, cardiac, and neurological ICUs. It has been a strong mortality predictor and literature over the years has documented the ability of the SOFA score to accurately distinguish survivors from non-survivors on admission. Over the years, multiple variations have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Propensity-score matching analysis pneumonia was assessed by the simplified CPIS (14)(15)(16) and the SOFA score (17)(18)(19) on the day of admission. Patients' comorbidities were evaluated by the CCI (20).…”
Section: Ia Group N=70mentioning
confidence: 99%
“…Propensity-score matching analysis pneumonia was assessed by the simplified CPIS (14)(15)(16) and the SOFA score (17)(18)(19) on the day of admission. Patients' comorbidities were evaluated by the CCI (20).…”
Section: Ia Group N=70mentioning
confidence: 99%
“…Kashyap et al investigated qSOFA and lactate during a larger review on the enhancement of sepsis identification scores, but did not study this tool in detail. 24 This review aimed to identify and provide high-level evidence as to whether lactate as an additive to qSOFA (LqSOFA) will enhance the rapid stratification of sepsis risk in adult patients with sepsis in various hospital settings, compared with qSOFA alone.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Kashyap et al investigated qSOFA and lactate during a larger review on the enhancement of sepsis identification scores, but did not study this tool in detail. 24 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the SOFA score on admission performed well for mortality prediction in sepsis in some studies (5,6), other studies have suggested only intermediate discriminatory accuracy (7,8). The use of SOFA score has also expanded beyond patients with sepsis (9,10) and is used outside of the ICU (6,11).…”
Section: Introductionmentioning
confidence: 99%